Determinasi Kompetensi Profesional dan Tantangan Adaptasi Sosial terhadap Kesiapan Mengajar Calon Guru Akuntansi di Era Society 5.0 - Mutiara Rahma; Siswandari Siswandari (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study aims to examine the urgency of strengthening the social and professional competencies of pre-service accounting teachers as a crucial factor in their teaching readiness amidst the complexities of Society 5.0. This focus was taken considering the low quality of teaching staff, which significantly affect the achievement of the Golden Indonesia 2045 target. Methods – Using a quantitative method with a multiple linear regression design. Population of Accounting Education students from the Faculty of Teacher Training and Education, Sebelas Maret University (UNS). A sample of 55 respondents was drawn through a purposive sampling technique with the criteria as follows: (1) they have passed a microteaching course and currently (2) Join an internship teaching program. Data were collected using a Likert-scale questionnaire and analyzed with regression correlation. Findings – The results showed that teacher competencies simultaneously contributed significantly to teaching readiness, accounting for 79.2% of the variance. Professional competency was identified as the strongest predictor (beta = 0.582) but recorded the lowest achievement level (81.1%) among all variables. Interestingly, although social competency correlated with readiness, social competency did not show a uniquely significant effect in the partial regression model (sig = 0.951).Research Implications – This study suggests that LPTK needs to reform the curriculum by strengthening the in-depth study of accounting material based on the latest industry standards, encouraging students to take competency certification, integrating problem-based learning practices, and being active in organizations or community service activities.